Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan PT Pegadaian (Persero) Cabang Sila Bolo Kabupaten Bima - Ibrahim Ibrahim; Ambo Paerah (Economy Deposit Journal (E-DJ), 2021)
Companies really need employees who have high productivity because employees are essentially one of the elements that become a resource in the company, these human resources who carry out daily activities. To realize employees who have high productivity need good leadership from above and also work motivation from their employees. This study aims to determine the effect of leadership and work motivation on the work of employees of PT. Pegadaian Sila Branch, Bima City. This research is an associative type with quantitative data from primary data sources. The data analysis technique used is validity test, reliability test, classical assumption test, regression analysis, correlation, determination test and t test. The results showed that leadership and work motivation together have an effect on the work productivity of the employees of PT. Pegadaian (Persero) Sila Bolo Branch, Bima City.